2017
DOI: 10.29252/jhs.5.3.58
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors Associated with Low Birth Weight

Abstract: Background and purpose:Since a large proportion of fetal mortality is associated with low birth weight (LBW) and considering the fact that fetal development is a vulnerable process influenced by maternal risk factors, this study examined some maternal risk factors associated with LBW infants. Materials and Methods:This cross-sectional study was conducted based on the medical records of 250 infants born in Zeynabeieh Hospital. The required data were registered in a pre-developed checklist. Then, the collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A higher level of maternal education may be associated with more healthy behaviours and better nutrition, which may lead to improvement in infant birth weight (12). Likewise, this was observed by some authors such as Hidalgo-Lopezosa et al ( 5), Jafari et al (27) or Tamura et al (28), who concluded that a high level of parental education acts as a protective factor for newborns that were small for their gestational age.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A higher level of maternal education may be associated with more healthy behaviours and better nutrition, which may lead to improvement in infant birth weight (12). Likewise, this was observed by some authors such as Hidalgo-Lopezosa et al ( 5), Jafari et al (27) or Tamura et al (28), who concluded that a high level of parental education acts as a protective factor for newborns that were small for their gestational age.…”
Section: Discussionmentioning
confidence: 67%
“…The birth weight of an infant is the first weight recorded after birth, ideally measured within the first hours after birth, before significant postnatal weight loss occurs (9,10). Low birth weight has been defined by the World Health Organization (WHO) as weight at birth of less than 2,500 grams (up to and including 2,499 g), irrespective of the gestation age (10)(11)(12)(13)(14)(15)(16). Low birth weight is further categorized into very low birth weight (<1,500 g) and extremely low birth weight (<1,000 g) (15,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59% of mothers had inadequate ANC visits whereas 38% had adequate visits which is comparable to other studies. 9,10,11 High number of inadequate ANC visits in the present study could be because of unavailability of easy access to proper health facilities in this part of the country. Most common complication in LBW neonates was neonatal sepsis (96%) followed by neonatal jaundice (87%), hypoglycemia (41%), apnea (17%), hypothermia (15%), birth asphyxia (13%), respiratory distress syndrome (12%), seizures (6%), pulmonary hemorrhage (3%), anemia (3%) and others (6% 20 In another study by Bhatnagar PK common causes of mortality were asphyxia neonatorum (40.18%), neonatal jaundice (39.26%), neonatal infections (15.88%), gastroenteritis (4.68%).…”
Section: Discussionmentioning
confidence: 73%